Epidemiology of recurrent hand, foot and mouth disease, China, 2008–2015 - Jiao, Huang; Qiaohong, Liao; Mong, How Ooi; Cowling, Benjamin J.; Zhaorui, Chang; Peng, Wu; Fengfeng, Liu; Yu, Li; Li, Luo; Shuanbao, Yu; Hongjie, Yu; Sheng, Wei (Centers for Disease Control and Prevention (CDC), 2018)
Using China’s national surveillance data on hand, foot and mouth disease (HFMD) for 2008–2015, we described the epidemiologic and virologic features of recurrent HFMD. A total of 398,010 patients had HFMD recurrence; 1,767 patients had 1,814 cases of recurrent laboratory-confirmed HFMD: 99 reinfections of enterovirus A71 (EV-A71) with EV-A71, 45 of coxsackievirus A16 (CV-A16) with CV-A16, 364 of other enteroviruses with other enteroviruses, 383 of EV-A71 with CV-A16 and CV-A16 with EV-A71, and 923 of EV-A71 or CV-A16 with other enteroviruses and other enteroviruses with EV-A71 or CV-A16. The probability of HFMD recurrence was 1.9% at 12 months, 3.3% at 24 months, 3.9% at 36 months, and 4.0% at 38.8 months after the primary episode. HFMD severity was not associated with recurrent episodes or time interval between episodes. Elucidation of the mechanism underlying HFMD recurrence with the same enterovirus serotype and confirmation that HFMD recurrence is not associated with disease severity is needed. © 2018, Centers for Disease Control and Prevention (CDC). All rights reserved.